An unsteady electro-magnetohydrodynamic two-liquid plasma flow along a channel of insulating porous plates with hall currents - Gowrisankara Rao, V.; Linga Raju, Temburu (Zielona Góra: Uniwersytet Zielonogórski)
It is proposed to use the Hall currents to model the transient magneto-hydrodynamic two liquid flows and heat transfer of ionized gases propelled by a common pressure gradient via a horizontal channel consisting of parallel porous plates. For the distributions of velocity and temperature, the principal partial differential equations that explain heat transfer flow under the chosen constraints are resolved.
Keywords: Hall effect; MHD heat transfer; plasma; immiscible flow; non conducting porous plates